CGIAR's science has informed and influenced the negotiations of the United Nations Convention on Biological Diversity and the final post-2020 Global Biodiversity Framework - Navarrete, Carolina; Demers, Nicole R. (2023)
With scientific and technical backstopping of CGIAR and other partners, for the first time, the Convention on Biological Diversity (GBF) has included a clear reference to the role of domesticated species diversity at the population level (Target 4), the role of agroecological approaches for the sustainable use of biodiversity in agriculture (Target 10), and has included means to monitor progress (Agrobiodiversity Index). The main users of the GBF are the member parties of the Convention on Biological Diversity.